2009
DOI: 10.4270/ruc.2009327
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of the International Financial Reporting Standards in Portugal: Can Expected Costs Be Reduced?

Abstract: In this paper we use a cost-benefit framework to discuss some of the expected effects related to the Portuguese adoption of the International Financial Reporting Standards (IFRS). Given the circumstances underlying this implementation, we anticipate that the overall net result following an analysis of costs and benefits will be negative. Therefore, we also examine what seems to be the causal factor behind this outcome and a potential way of reducing the net cost of adopting the IFRS. The costs are related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…La mayoría de los artículos publicados de los años 2008 y 2009 se concentraron en los temas más generales; muchas investigaciones atendieron el tema de la evolución del concepto del valor justo en las normas brasileña con un análisis gradual e histórico del desarrollo de estas normas dentro del concepto fair value (Castro, Morch, & Marques, 2008;Murcia et al, 2008), algunos autores escribieron sobre las inferencias económicas, a priori, de las reglamentaciones nacionales en consonancia con los estándares internacionales (Fernandes et al, 2008;Ito, Mendes & Niyama, 2008;Strouhal, 2009;Alves & Moreira 2009;Pereira & Marques, 2009;Barbosa, Dias & Pinheiro, 2009;Silva, Couto & Cordeiro, 2009;Fuji, 2008;Santos & Cia, 2009). En el período 2009-2013 se destacan los estudios que arman que la convergencia para los estándares contables internacionales es un asunto relevante, desarrollando comparaciones de los pronunciamientos técnico CPC con cada una de las Normas Internacionales, con el objetivo de vericar diferencias entre estos dos sistemas de reglas.…”
Section: Tablaunclassified
“…La mayoría de los artículos publicados de los años 2008 y 2009 se concentraron en los temas más generales; muchas investigaciones atendieron el tema de la evolución del concepto del valor justo en las normas brasileña con un análisis gradual e histórico del desarrollo de estas normas dentro del concepto fair value (Castro, Morch, & Marques, 2008;Murcia et al, 2008), algunos autores escribieron sobre las inferencias económicas, a priori, de las reglamentaciones nacionales en consonancia con los estándares internacionales (Fernandes et al, 2008;Ito, Mendes & Niyama, 2008;Strouhal, 2009;Alves & Moreira 2009;Pereira & Marques, 2009;Barbosa, Dias & Pinheiro, 2009;Silva, Couto & Cordeiro, 2009;Fuji, 2008;Santos & Cia, 2009). En el período 2009-2013 se destacan los estudios que arman que la convergencia para los estándares contables internacionales es un asunto relevante, desarrollando comparaciones de los pronunciamientos técnico CPC con cada una de las Normas Internacionales, con el objetivo de vericar diferencias entre estos dos sistemas de reglas.…”
Section: Tablaunclassified
“…Between 2004 and 2006, Portuguese listed companies had to concentrate their efforts on the necessary changes to adopt the IFRS. Alves and Moreira (2009) argue that costs underlying the adoption of the IFRS in Portugal are related to the professional updating of accounting skills of those directly or indirectly involved in the accounting process. Compared with the national accounting framework, the IFRS are much more complex and, although some professionals may already have some knowledge of IFRS usage, for most it will be a new and costly issue (Alves and Moreira, 2009, p. 160).…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Compared with the national accounting framework, the IFRS are much more complex and, although some professionals may already have some knowledge of IFRS usage, for most it will be a new and costly issue (Alves and Moreira, 2009, p. 160). According to Alves and Moreira (2009), a part of these costs will be incremental and permanent over time due mainly to the fact that two accounting systems will be kept in place. It is very likely that non-financial disclosures such as those concerning intellectual capital became less important in terms of Portuguese companies' performance disclosure strategies.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…On the other hand, few others have also suggested that IFRS may be problematic in several ways. First, IFRS encourage small and medium enterprises to cover unnecessary expenses in order to implement it [2]. Second, IFRS has not yet been able to prove to produce better accounting qualities [1].…”
Section: Introductionmentioning
confidence: 99%